Maritime policy, management and research : role and potential - Panayides, Photis (My University, 2006)
This special issue of Maritime Policy and Management includes a collection of the best papers presented at the recent conference of the International Association of Maritime Economists (IAME) 2005. On the basis of a review and conceptual synthesis of the six papers selected for the special issue, this paper provides a discussion of the role and potential of research in informing managerial decision-making and policy-making in the context of the maritime industry and makes recommendations for elevating the discipline-related credentials of the maritime area as a field of study
Keywords: Management--Research; Transportation; Shipping